Does Intelligence Affect Economic Diversification? - Oasis Kodila-Tedika; Simplice A. Asongu (African Governance and Development Institute (AGDI), 2014)
This paper extends the growing literature on knowledge economy by investigating the effect of intelligence on economic diversification. Using a battery of estimation techniques that are robust to endogeneity, we find that human capital has positive correlations with export diversification, manufactured added value and export manufactures. This empirical evidence is based on a world sample for the year 2010. The findings have significant implications for the fight against the Dutch disease. In essence, investing in human capital could bring economic diversity and therefore dampen negative external shocks related to resource-dependence. Other knowledge-economy implications are discussed.
Keywords: O1; O4; O55; I32; I2; 330; Intelligence; Economic Diversification